NETWORK ASTRONOMY FOR SCHOOL EDUCATION BASED ON ETHNOASTRONOMY FOR ASTRONOMY LEARNING: A LITERATURE REVIEW - Pujianto, Pujianto; Husna, Salsabila; Azzahra, Talitha Rahma; Setiaji, Bayu; Aziz, Khafidh Nur; Maharani, Devinda Putri; Nugroho, Kuncoro Asih (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
The research in this article aims to review the available literature on integrating ethnoastronomy-based NASE on the understanding and trust of teachers, students, and society. The method used in this study is a literature review from 2010-2022, which strictly discusses the challenges in learning astronomy and astronomy in local wisdom with two questions that need to be answered, namely (1) what kind of challenges are faced when conducting astronomy learning and does NASE influence astronomy learning? (2) Does local wisdom relate to astronomical learning, and how does the community's understanding and beliefs relate to Ethnoastronomy? The results of the literature review stated that NASE has a positive influence on the challenges of learning astronomy, NASE has a relationship with local wisdom that discusses astronomy, and this research also shows that the relationship between local wisdom and astronomy with NASE can increase people's understanding and trust in Ethnoastronomy from each culture they have. This article recommends that astronomy-based NASE integrated learning with local wisdom can be applied in various countries, especially astronomy learning in Indonesia, so that the culture owned is preserved due to the times and can be used for learning.